Characterization of a monothiol glutaredoxin encoded by Chlorella virus PBCV-1 - Fitzgerald, Lisa A. (2009)
Annotation of the 330-kb Chlorella virus PBCV-1 genome identified a 237 nucleotide gene (a438l) that codes for a protein with ~35% amino acid identity to glutaredoxins (Grx) found in other organisms. The PBCV-1 protein resembles classical Grxs in both size (9 kDa) and location of the active site (N-terminus). However, the PBCV-1 Grx is unusual because it contains a monothiol active site (CPYS) rather than the typical dithiol active site (CPYC). To examine this unique active site, four site-specific mutants (CPYC, CPYA, SPYC, and SPYS) were constructed to determine if the N-terminal cysteine is necessary for enzyme activity. Wild type and both mutants containing N-terminal cysteines catalyzed the reduction of disulfides in a coupled system with GSH, NADPH, and glutathione reductase. However, both mutants with an altered N-terminal cysteine were inactive. The grx gene is common in the Chlorella viruses. Molecular phylogenetic analyses of the PBCV-1 enzyme support its relatedness to those from other Chlorella viruses and yet demonstrate the divergence of the Grx molecule.